Chapter 8 Divergent Ambitions Bracketing the Disruptive Potential of Transitional Justice in Belgium - Destrooper, Tine (Taylor & Francis, 2023)
This chapter compares two attempts to apply transitional justice to Belgium: the special parliamentary commission established in 2020 to analyse Belgium's colonial past in the Great Lakes region; and the earlier process of designing an educational programme for dealing with societal polarization. The parliamentary commission was modelled on a truth commission, while the educational programme drew on experiences with using transitional justice tools in conflicted settings in the Global South. Where the first struggled with issues of representation and decoloniality, the second met with skepticism and rejection because transitional justice was understood to apply to the Global South. Inscribed in these responses to transitional justice were therefore the relationship between Belgium and its others in the Global South. The chapter demonstrates that in consolidated democracies engaging in transitional justice processes may challenge the legitimacy of existing state institutions and their associated narratives.